An improved gate allocation mechanism for better runway optimisation - Ong, Yan Jie (2015)
Strong demand for air transportation services is indicative of business expansion to exploit consumption. The industry nature however spells high capital investment and long lead times, two factors that if poorly managed, will cause service providers to falter in capturing the ballooning market share. Airports in particular face a multitude of international rules, regulatory bodies and territorial space limitations that constrains explorable options to a limited few. A quicker and more cost-efficient method is to optimise operations within current infrastructure to achieve higher utilisation rates, thereby increasing capacity without extra cost. This report studies optimisation of an airport runway or runway throughput, a sub-functional group in airport operations often identfied to be a bottleneck. Current gate allocation practices are examined for its correlation and effectiveness in contributing to improving runway throughput. An improved gate allocation model built on linear programmig techniques is proposed to achieve runway optimisation. The model is implemented in General Algebraic Modelling System (GAMS) modelling environment, and parameters obtained from real-life historical data is used as inputs to establish a baseline. The results are then analysed with respect to the benchmark, and its effectiveness concluded.